(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
Abstract This study aims to find out and understand what the driver’s position is like in a partnership agreement with online transportation entrepreneurs and what are the legal forms of protection, the criteria for potential partnership agreement disputes with entrepreneurs providing online application-based applications. This thesis research uses Legal Research with the type of normative legal research, which is a study that examines the law based on statutory regulations and is supported by the addition of case approach data that uses primary legal material sources, namely as the main basis used in The framework of this research is the Civil Code and other related regulations and the second is secondary legal material, namely legal material that is closely related to primary legal materials such as research results, works from legal circles, and other documents related to partnership agreements. Abstrak Penelitian ini bertujuan untuk mengetahui dan memahami seperti apakah kedudukan pengemudi dalam perjanjian kemitraan dengan pengusaha transportasi online dan apa sajakah perlindungan bentuk hukum kriteria adanya potensi perselisihan perjanjian kemitraan dengan pengusaha penyedia aplikasi berbasis aplikasi online. Penelitian skripsi ini menggunakan Penelitian Hukum (Legal Research) dengan tipe penelitian hukum normatif, yaitu suatu penelitian yang mengkaji ‎hukum berdasarkan peraturan perundang-undangan serta didukung oleh ‎penambahan data pendekatan case yang menggunakan sumber bahan hukum primer yaitu sebagai landasan utama yang dipakai dalam rangka penelitian ini adalah Kitab Undang-Undang Hukum Perdata dan Peraturan lainnya yang berkaitan dan yang kedua yaitu bahan hukum sekunder yaitu bahan hukum yang erat kaitannya dengan bahan hukum primer seperti hasil penelitian, hasil karya dari kalangan hukum, serta dokumen lain yang berkaitan dengan perjanjian kemitraan.